Pengembangan Media Pop-Up Book Berbasis Budaya Lokal Keberagaman Budaya Bangsaku Siswa Kelas IV Sekolah Dasar - Muhammad Sholeh (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
The purpose of this research is the development of local culture-based Pop-Up Book media based on process skills to train students' confidence that is valid, practical and effective. Focus on the PPKn class IV load, the sub-theme of my national culture diversity. This type of research uses the ADDIE development model (analysts, design, development, implementation, evaluation). The research subjects were fourth grade students of elementary school. The results of the local culture-based Pop-Up Book media validation of Grade IV elementary school students are (1) Local culture-based Pop-Up media have teaching material that has a movable part with two-dimensional elements. (2) Fulfilling valid criteria with the results of the material expert test reaching a 97% validity level with the category of